Construction stage analysis of a precast concrete buried arch bridge with steel outriggers from full-scale field test. (February 2021) - Jeon, Seok Hyeon; Moon, Hong Duk; Sim, Chungwook; Ahn, Jin-Hee
Abstract: A new type of Precast Concrete buried Arch bridge with Steel Outriggers (PCASO) was developed to maximize the structural efficiency and improve the constructability of a precast concrete arch system buried underground. In this study, a full-scale field test of Precast Concrete buried Arch bridge with Steel Outriggers (PCASO) was conducted to evaluate the strain and stress state and deformation observed on the concrete panels and steel outriggers during the various construction stages, namely, when the panels were being lifted, and when backfill was being placed on the arch in three stages. The field specimen spanned 6 m and was 2 m high. Displacements were observed in both the vertical and horizontal directions during the backfill construction. However, the final position of the arch was achieved when topsoil was placed on the precast panels. The compressive strains observed on the precast panels increased as the soil was being placed. After the backfill was completed and the topsoil was emplaced, the maximum compressive strains measured on the precast panels were approximately 19% of the compressive strength (which was 8 MPa). During the construction stage, the steel outriggers experienced maximum tensile stresses of approximately 300 MPa, which is close to the service stress level of steel (whose yield strength is 413 MPa). Considering that the outriggers were constructed with thin steel plates and there was little stress change during different construction stages, the nominal stress of the thin plate was checked. The calculated nominal stress based on the measured compressive and tensile stresses ranged between positive and negative 25 MPa. A finite element analysis was conducted following the construction stages of the field test using the field parameters. The analytical study demonstrates that the changes in stress and displacement for each construction stage are comparable between the field measurements and the numerical calculations. Overall, this study validated the structural behaviors of the new type of PCASO through field demonstrations and finite element analyses.